Project VUE: Visualizing Urban Equilibrium - Meihaus, Michael Brennan (Kansas State University, 2009)
Visualizing Urban Equilibrium is a landscape architecture master’s project and report intended to enhance the collective hydrologic, social, and aesthetic functions of Kansas State University’s Campus Creek corridor. The highly urbanized conditions of the approximately 1.4 mile channel and 408 acre sub-watershed are the result of neglect for stable hydrologic function, poor campus planning, and a disregard for cohesive form and function of natural aesthetics on campus. This proposal aims to balance goals of enhanced hydrologic function with those of campus social and aesthetic function into one cohesive process of landscape planning and design. Synthesizing complex social fabrics with proper urban watershed assessment and management, as well as natural geomorphic channel design re-envisions of sense of harmony and place within a major campus corridor and green space. Communication of this proposal takes the form of a Comprehensive Campus Creek Corridor Plan, for a rapidly developing academic institution and community. This plan centralizes the creek on campus and includes urban-watershed assessment, site specific conceptualizations of storm-water best management practices, and detailed channel enhancement for improved hydrologic function. Social function is enhanced through integration of pedestrian oriented planning, and education oriented spatial design opportunities for increased interaction with and within the Campus Creek corridor. Enhancement of aesthetic function includes management for a balance of formal and natural character, re-established visual connectivity and sense of place, as well as installation of landscape improvements and artistic expressions of the “equilibrium” paradigm defining the creeks natural function and its urban context. Included in this masters project and report is a project introduction and premise, Campus Creek site inventory and sub-watershed assessment, programming for improvements, and visualization of the conceptual comprehensive plan and site design elaborations.
Keywords: campus creek; enhancement; urban; stream; campus; creek; Landscape Architecture (0390)